Usability Analysis of A Package Tracking System Using The System Usability Scale Method - Asnawi, Noordin; Lenawati, Mei; Pamungkas, Ridho; Setiawan, Dimas (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The Main Branch Post Office (Kantor Pos Cabang Utama, KCU) Madiun, as part of the Pos Indonesia network, plays a key role in managing parcel deliveries, document handling, and financial transactions in Madiun and surrounding areas. The delivery process includes three main stages: First Mail, Middle Mail, and Last Mail. In the First Mail stage, mail and parcels are collected at counters from various sources such as post offices, mailboxes, or customers. In the Middle Mail stage, items are sorted by officers based on their final destinations. Finally, in the Last Mail stage, parcels are sorted again by specific routes or locations within the city before being delivered directly to recipients by couriers.This research focuses on evaluating and improving the user interface of the